Bibliometric analysis of scientific research on repeat visit intention in tourism using visual mapping technique - Félix Díaz-Pompa; Gül Erkol Bayram; Beatriz Vega-Pérez; Beatriz Serrano-Leyva; Hatice Sarı Gök; Ali Turan Bayram (Tourism and Hospitality Management, 2025)
Purpose – The purpose of this study is to examine the status of scientific research on “revisit intention” in the Scopus database through a systematic literature review using key indicators. Methodology/Design/Approach – In this study, studies on revisit intention between 2007 and 2022 were analysed using bibliometric methods with the help of Rstudio.cloud software. In this research, general information about the publications, citation analysis, trend topic analysis, cross-country cooperation analysis, thematic analysis, and multiple correspondence analysis were conducted. Findings – Results – The sample of the study consists of 280 studies from 149 sources that include “revisit intention” in the title, abstract and keywords of articles in journals scanned in the Scopus database. It has been determined that there has been an increase in research on the research topic in recent years, and the highest scientific production was published in 2022 with 76 research. The highest number of research on revisit intention was published in the Sustainability journal (41 research), and China is the country with the most scientific publications. The most productive author with 6 research on the research topic is Ramayah Thurasamy. The strongest collaboration lines are those between China, Australia, Korea, the United Kingdom and the United States. The topics that researchers mostly address regarding revisit intention are destination image, service quality, perceived value, customer satisfaction, and the effects of COVID-19. Originality of the research – The study employs advanced bibliometric tools to systematically map the field’s evolution and identifying emerging post-pandemic trends. By integrating these findings, it offers actionable frameworks for tourism strategy design and prioritizes understudied areas such as memorable experiences and sustainability-driven loyalty models to guide future research agendas